Dihydromyricetin resists inflammation‐induced muscle atrophy via ryanodine receptor‐CaMKK‐AMPK signal pathway. Issue 21 (22nd October 2021) - Hou, Lianjie; Jiang, Fangyi; Huang, Bo; Zheng, Weijie; Jiang, Yufei; Cai, Gengyuan; Liu, Dewu; Hu, Ching Yuan; Wang, Chong
Abstract: Skeletal muscle plays a pivotal role in the maintenance of physical and metabolic health. Skeletal muscle atrophy usually results in physical disability, inferior quality of life and higher health care costs. The higher incidence of muscle atrophy in obese and ageing groups is due to increased levels of inflammatory factors during obesity and ageing. Dihydromyricetin, as a bioactive polyphenol, has been used for anti‐inflammatory, anti‐tumour and improving insulin sensitivity. However, there are no published reports demonstrated the dihydromyricetin effect on inflammation‐induced skeletal muscle atrophy. In this study, we first confirmed the role of dihydromyricetin in inflammation‐induced skeletal muscle atrophy in vivo and in vitro. Then, we demonstrated that dihydromyricetin resisted inflammation‐induced skeletal muscle atrophy by activating Ca 2+ ‐CaMKK‐AMPK through signal pathway blockers, Ca 2+ probes and immunofluorescence. Finally, we clarified that dihydromyricetin activated Ca 2+ ‐CaMKK‐AMPK signalling pathway through interaction with the ryanodine receptor, its target protein, by drug affinity responsive target stability (DARTS). Our results not only demonstrated that dihydromyricetin resisted inflammation‐induced muscle atrophy via the ryanodine receptor‐CaMKK‐AMPK signal pathway but also discovered that the target protein of dihydromyricetin is the ryanodine receptor. Our results provided experimental data for the development of dihydromyricetin as a functional food and new therapeutic strategies for treating or preventing skeletal muscle atrophy.